Royal Commission on Equal Pay - TUC evidence, 1945 (1945)
1945 1945-1960 "Royal Commission on Equal Pay - TUC evidence, 1945" [EP0079], 1945 The TUC memorandum of evidence to the Royal Commission includes a detailed survey of men's and women's rates of wages in different industries and occupations 1939-1945.